Ebola virus disease in children in Sierra Leone: a retrospective cohort study. (25th February 2016) - Fitzgerald, Felicity; Naveed, Asad; Wing, Kevin; Gbessay, Musa; Ross, Gareth; Checchi, Francesco; Youkee, Daniel; Jalloh, Mohammed; Baion, David; Mustapha, Ayeshatu; Jah, Hawanatu; Lako, Sandra; et al.
Abstract: Background: The outbreak of Ebola virus disease in West Africa has claimed more than 11 200 lives with more than 28 000 cases. Infected children under the age of 5 years have a high mortality rate but little is known about disease progression and possible predictors of outcome. Circumstantial factors such as transfer distances from Ebola holding units to Ebola treatment centres and admission with a caregiver might affect outcome. We aimed to identify clinical, epidemiological, and management risk factors for mortality in children with Ebola virus disease. Methods: Children under the age of 12 years admitted to 11 Ebola holding units in the Western Area of Sierra Leone from Aug 1, 2014, to April 1, 2015, were eligible for inclusion. Retrospective data were collected from site admission books, case investigation forms, and clinical records, and cross-referenced with district-wide laboratory results, burial records, child protection records, staff interviews, and telephone calls to guardians. Univariate and multivariate analyses were used to identify features independently associated with mortality. Findings: 309 children with Ebola virus disease (aged 2 days to 12 years) were admitted (median age 6 years, IQR 3–10). Outcomes were available for 282 children (91%). 161 children (57%) died with 89 deaths (55%) occurring at Ebola holding units and 72 (45%) at Ebola treatment centres. Marked derangement of white cell count, C-reactive protein, and renal and liver function were seen with extensive hypoglycaemia. Up to 60% of children were admitted without a caregiver. Factors that potentially affected mortality such as age, clinical features, delayed attendance, transfer distance, caregiver accompaniment, and medications received are being examined. Multiple imputation is being performed to account for missing data. Interpretation: This is the most comprehensive paediatric cohort of Ebola virus disease to date, and the only cohort to incorporate data from both Ebola holding units and Ebola treatment centres. Data sharing between sites is crucial to identify potentially modifiable risk factors and guide future operational responses. Funding: This study was funded by Save the Children and supported by the Medical Research Council and the National Institute for Health Research Biomedical Research Centre at Great Ormond Street Hospital for Children NHS Foundation Trust and University College London.